Mobilidade populacional na produção do espaço metropolitano regional : o caso de Fortaleza - Araújo, Ana Maria Matos (2007)
The overpopulation of all metropolises is a well-known fact and aspired as an urban and modern way of living. The metropolises offer better living conditions in terms of jobs, homes, transportation comfort, communication, leisure and entertainment, culture and political expression. Contradictorily, metropolises are a mixture of opulence and poverty, that is reproduced spatially. Capitalist accumulation produces the mobility of work and the population at the same time in which it generates social-territorial inequalities. The metropolitan citizen, especially the unemployed workers, the sub-employed, and the autonomous workers, are subject to constant compulsory or voluntary space displacements, producing spatiality and territoriality in the downtown and periphery direction. The slums and the private restricted condominiums of the upper classes are manners of current occupation of the Brazilian metropolitan periphery. But today the periphery is not only in the physical occupation of the metropolis or of its region. It increases the social-cultural hiatus among the classes, and thus, both the popular neighborhoods and the slums can be places peripheral to capitalist dominance of the space, as they become neighbors and central, in landscape and territorial terms, demanding (according to the dominant capitalist perspective) space restructuring for change of uses and of the valorization of the area, or of the neighborhood. Metropolitan workers changed their classic housing strategies. Besides self constructions and the irregular division of land into lots, they adopted the invasions of public and private properties, of areas of permanent environmental preservation, appropriating several places of the metropolis as a solution for their needs not just for a home, but for the reproduction of their workforce. The immense housing deficit produced in the metropolitan popular classes feeds this popular housing market, that is part of the real estate market as a whole in spite of being a non-capitalist production. This was the discussion that was carried out in this thesis starting from the study of the case of nine slums that were invaded and occupied by workers in the metropolis of Fortaleza and in 16 slums of six municipal districts of the outskirts of the metropolitan area, totaling 801 interviewed families. It was through the method of critical geography and following the techniques of observation of the social spatial structures, aided by the analysis of social-demographic indicators and speeches of the inhabitants with the interpretation of the relative conflicts pertaining to the compulsory displacements of the families that the population mobility was understood as a basic contemporary phenomenon of capitalist valorization of the space associated to the more global capitalist valorization. Confirming, therefore, some theoretical presuppositions adopted initially, that there would be a more general relationship, between mobility of the population, metropolitan space and capitalist accumulation.